Ecosystem Services: A Systematic Literature Review and Future Dimension in Freshwater Ecosystems - Deeksha; Shukla, Anoop Kumar (Applied sciences, 2022)
Ecosystem services are part and parcel of human lives. It is of paramount importance to understand the interaction between these ecosystem services, as they are directly related to human life. In the modern era, quantification of ecosystem services (ES) is playing an important role in the proper understanding and efficient management of social–ecological systems. Even though a significant amount of literature is available to present on the topic, there is a need to build an adequate amount of knowledge repository. Hence, a systematic literature review method is used, in which research question and searching stages are defined. This review study is conducted on ecosystem services and remote-sensing-related keywords in the Scopus database. After a systematic analysis of the papers retrieved from the Elsevier, Scopus database, MDPI, and open source, a total of 140 primary articles were categorized according to their relationship with other ecosystem services, land use, land cover, and planning management. Major issue findings and important aspects have been analyzed and reported in each category. With this analysis and developments in the existing literature, we have potential areas for future research. Findings pointed out that regional or local-level ecosystem services-related work is immensely important, and a hotspot of current research aiming to understand the variability and spatiotemporal dynamics in terrestrial and aquatic ecosystems.